Mental Health Consumers’ Motives for Seeking Advocacy Support: A Qualitative Exploration - Stomski, N.; Morrison, P.; Whitely, Martin; Brennan, P. (Springer New York LLC, 2018)
© 2017, Springer Science+Business Media, LLC. Advocacy plays a vital role in ensuring that mental health consumers’ rights are maintained. However, the primary issues for which consumers seek advocacy support remain unknown. Understanding these issues provides a sound basis from which advocacy organisations may develop a clear service delivery focus. This study addresses the literature gap through presenting a qualitative analysis of 60 records from an advocacy service. Four major themes emerged, across which two key issues were dominant: the sense of fearfulness and disempowerment. These issues accentuate the importance of advocates in enhancing the agency of mental health consumers.